Gender identity and brand incongruence: when in doubt, pursue masculinity. (28th July 2016) - Neale, Larry; Robbie, Renee; Martin, Brett
Abstract : Gender identity is the extent to which an individual identifies with masculine or feminine personality traits. Sex roles in Western societies continue to evolve, so this research examines the developing relationship between gender identity and consumer responses to gendered branding. Grounded in self-congruency theory [Sirgy, M. J. (1982). Self-concept in consumer behavior: A critical review. Journal of Consumer Research, 9, 287–300], the present research reports an experiment that supports a congruence relationship between gender identity and brand response. Masculine consumers prefer masculine brands. The results also show incongruent brand rejection where masculine consumers react negatively to feminine brands although feminine consumers are more accepting of masculine brands. Further, the results suggest that gender identity is a more effective dimension for customer segmentation than biological sex. Overall, the results suggest that masculine brands are more effective than other gendered brand profiles for masculine, feminine, and androgynous consumers.